A clinical evaluation of bleeding patterns, adverse effects, and satisfaction with the subdermal etonogestrel implant among postpartum and non-postpartum users - Abdul Wahab, Noraziana; A. Rahman, Nor Azlina; Mustafa, Kamarul Bahyah; Awang, Mokhtar; Sidek, Ayu Aszliana; Mohd Rus, Razman (Elsevier BV, 2016)
The etonogestrel implant (Implanon; Merck Sharp and Dohme, Kenilworth, NJ, USA) is an effective contraceptive with a good safety profile for up to 3 years [1]. However, its adverse effects include irregular vaginal bleeding (affecting 68.0% of users), weight gain (20.7%), acne (15.3%), breast pain (9.1%), and headache (8.5%) [2]. To provide further information about contraception options for women in the postpartum period, the aim of the present study was to investigate the bleeding patterns and adverse effects reported by women who underwent Implanon insertion within 8 weeks of delivery and compare them with those experienced by non-postpartum women.